Flight training-induced stage-specific reorganization of the ventral visual network in pilots: evidence from longitudinal and cross-sectional studies - Zhang, Shicong; Chen, Xi; Guo, Shuqi; Zhang, Zhuyu; Xu, Peiran; Meng, Qingbin; Hao, Jiaqi; Chu, Qi; Li, Xiuyi (Brain and cognition, 2025)
•This study used both longitudinal and cross-sectional designs to assess pilot brain plasticity.•Graph-theoretical analysis was applied to multimodal MRI to examine visual network topology.•Flight cadets showed reduced clustering coefficient and local efficiency in the ventral network.•Expert pilots showed decreased small-worldness and global efficiency in the ventral stream. Aviation safety critically depends on pilots’ visual processing abilities. Understanding the plasticity of its neural mechanisms can inform flight training optimization. This study used longitudinal and cross-sectional designs to investigate how long-term flight training affects functional reorganization within the ventral and dorsal visual networks. Multimodal MRI data were collected from 136 participants across two experiments: Experiment 1 (25 flight cadets, 24 controls) and Experiment 2 (48 pilots, 39 controls). Longitudinal analysis showed that cadets exhibited a significant decrease in ventral network clustering coefficient and local efficiency after three years of training (population × time interaction). Cross-sectional results revealed that professional pilots had reduced small-worldness and global efficiency in the ventral network, both negatively correlated with flight hours, while characteristic path length was positively correlated. No significant differences were observed in the dorsal visual network. These findings suggest that flight training induces stage-specific topological remodeling of the ventral visual network, possibly through local pruning and enhanced global integration. Moreover, the ventral network demonstrates greater sensitivity to flight-related experience than the dorsal pathway. This study advances understanding of neural adaptation in aviation and offers insights into stage-specific training strategies for optimizing pilot performance.